2021
DOI: 10.1080/13696998.2021.1885418
|View full text |Cite
|
Sign up to set email alerts
|

Real-world impact of brain metastases on healthcare utilization and costs in patients with non-small cell lung cancer treated with EGFR-TKIs in the US

Abstract: View related articles View Crossmark data Real-world impact of brain metastases on healthcare utilization and costs in patients with non-small cell lung cancer treated with EGFR-TKIs in the US Economic burden of brain metastases in NSCLC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similarly, on the basis of 23 observational studies, a range of 12.3–81.5% patients were reported to have asymptomatic brain metastases at baseline (Table 3 ). Among the three observational studies that reported symptoms, headache, nausea, and mental changes were the most frequently reported [ 30 , 46 , 64 ]. Patients who were asymptomatic were more likely to have been treated with EGFR TKIs only or EGFR TKIs plus SRS compared with patients who were treated with WBRT alone or in combination with another type of therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, on the basis of 23 observational studies, a range of 12.3–81.5% patients were reported to have asymptomatic brain metastases at baseline (Table 3 ). Among the three observational studies that reported symptoms, headache, nausea, and mental changes were the most frequently reported [ 30 , 46 , 64 ]. Patients who were asymptomatic were more likely to have been treated with EGFR TKIs only or EGFR TKIs plus SRS compared with patients who were treated with WBRT alone or in combination with another type of therapy.…”
Section: Resultsmentioning
confidence: 99%